(untitled) (Collection of scientific works «Modern structures of metal and wood», 2021)
The article considers the features and advantages of innovative design and technology solution for mini-hotels construction in the framework of eco-tourism development. The examination of the main potentials of eco-tourism development in Ukraine and Moldova, are presented on the example of the city of Tiraspol. Space planning and design features of the project "Dubovaya Roshcha" tourist complex in Tiraspol, Moldova are characterized there. This article presents a method of multicriteria analysis of design and technology solutions based on the factor evaluation of decision options of low-rise building construction. In this examination the main factors influencing the choice of building structures were emphasized.